Referral of suspected colorectal cancer: have guidelines made a difference? - Jiwa, Moyez; Hamilton, W. (Royal College of General Practitioners, 2004)
In the United Kingdom, patients with colorectal symptoms referred on the fast-track pathway into secondary care are offered investigation of their symptoms within 2 weeks. Audits demonstrate that a minority of patients with colorectal cancer are referred under this arrangement. We assessed referral letters to hospitals in one district in the period before and after the introduction of the 2-week wait initiative. The guidelines appear to have made little difference to the proportion of cases selected for referral on the urgent pathway. However, cancers in the earliest stages present with fewer clinical features than advanced disease and a combination of signs and symptoms are more likely to arouse suspicion in the referring agent.